Biology and morphometry of Paracoccus marginatus Williams and Granara de Willink (Hemiptera: Pseudococcidae) - Chellappan, Mani; Lawrence, Lince; Ranjith, M.T. (ENTOMON, 2015)
Biology and morphometry studies of Paracoccus marginatus Williams and Granara de Willink (Hemiptera: Pseudococcidae) on papaya (Carica papaya L), jatropha (Jatropha curcus L.), mulberry (Morus alba L.), and potato (Solanum tuberosum L.) were carried out in AINPAO laboratory, College of Horticulture, Kerala Agricultural University, Vellanikkara. Among the four host plants, P. marginatus on papaya recorded the highest pre-imaginal periods (egg to third instar nymphs in females and egg to pupa in males) for both females and males, whereas the lowest pre-imaginal period was observed on potato. Female P. marginatus recorded the highest and lowest adult longevity on papaya and jatropha respectively. The fecundity of P. marginatus on the four host plants varied in the order, papaya > potato > jatropha > mulberry. On papaya, mulberry and jatropha, the sex ratio of P. marginatus was more male-biased whereas on potato it was slightly female-biased. A non significant variation was observed on morphometrics (length and width) of all stages of male and female P. marginatus on four different host plants.